Non-Revenue Water in Water Supply Systems of Serbia and Montenegro - Dejan Dimkić; Marko Babalj; Darko Kovač; Mira Papović (Environmental Sciences Proceedings, 2022)
Non-revenue water (NRW) can be expressed using different parameters (indices) in certain water supply systems (WSSs). The most used are percentages (as a share of NRW in system input water) and the infrastructure leakage index (ILI) based on the IWA methodology. The technical indicator of real losses (TIRLs) is also an index used for the estimation of certain WSS efficiency. Both real and apparent losses are significant in many WSSs in the Balkan region. Thirty-seven WSSs in Serbia and Montenegro, which differ in many aspects, were analyzed. After presenting the methodology and discussing the results, a conclusion is drawn, as well as general guidelines regarding the approach for the reduction of NRW for this region.